The roles of small RNAs in rice-brown planthopper interactions - Jing, Shengli; Xu, Jingang; Tang, Hengmin; Li, Peng; Yu, Bin; Liu, Qingsong (Frontiers in Plant Science, 2023)
Interactions between rice plants (Oryza sativa L.) and brown planthoppers (Nilaparvata lugens Stål, BPHs) are used as a model system to study the molecular mechanisms underlying plant-insect interactions. Small RNAs (sRNAs) regulate growth, development, immunity, and environmental responses in eukaryotic organisms, including plants and insects. Recent research suggests that sRNAs play significant roles in rice-BPH interactions by mediating post-transcriptional gene silencing. The focus of this review is to explore the roles of sRNAs in rice-BPH interactions and to highlight recent research progress in unraveling the mechanism of cross-kingdom RNA interference (ckRNAi) between host plants and insects and the application of ckRNAi in pest management of crops including rice. The research summarized here will aid in the development of safe and effective BPH control strategies.